Conjunctions in some english marketing newsletters (With reference to Vietnamese equivalents) / Tran Thi Thuong; Supervisor: Assoc. Prof. Dr. Phan Van Que - Tran, Thi Thuong
ABSTRACT Nowadays, English plays a key role in everyday life communication as well as in exchange of ideas in terms of culture, society, economy, politics and business all over the world. As a result, we need to enhance the mastering of principles in English usage. In learning English, grammar is an important factor and normally carefully considered. Besides, conjunctions have been one of the most fascinating topics that attract a large number of people. It is one of the four main categories of adverbials and it plays an important role in joining phrases, clauses, sentences in order to create coherence in every text. So, this study investigates how learners of English and Vietnamese use the conjunctions in some marketing newsletters. The writer use two main research approaches. They are quantitative and qualitative. Data used in this study are collected from various sources some English magazines, marketing newsletters in English and Vietnamese, internet, media as well as other related research. To obtain the main objectives of the study which is to show the similarities and differences of the conjunctions in English and Vietnamese marketing Newsletters. The results show that in conjunctions, both two languages have the same kinds. However, they have some kinds and the usages are not the same in English and Vietnamese. The writer would like to conduct this research with the hope that our study can bring some theoretical and practical value for both linguistic study and language teaching methodology.